2021
DOI: 10.1016/j.cmi.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of human metapneumovirus infection in adults hospitalized for community-acquired influenza-like illness in France, 2012–2018: a retrospective observational study

Abstract: Objectives: To describe the prevalence, clinical features and complications of human metapneumovirus (hMPV) infections in a population of adults hospitalized with influenza-like illness (ILI). Methods: This was a retrospective, observational, multicenter cohort study using prospectively collected data from adult patients hospitalized during influenza virus circulation, for at least 24 h, for communityacquired ILI (with symptom onset <7 days). Data were collected from five French teaching hospitals over six con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
3
13
1
Order By: Relevance
“…In our study, 6.2%, 10.9%, and 17.3% of patients hospitalized with influenza, RSV, and hMPV died within 30 days following admission, respectively. These mortality rates were consistent with those in prior studies of older adults hospitalized with these three viral infections [18,26,27]. Many studies to date have assessed disease severity associated with these three types of viral infections, but the results of these studies have been highly varied.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, 6.2%, 10.9%, and 17.3% of patients hospitalized with influenza, RSV, and hMPV died within 30 days following admission, respectively. These mortality rates were consistent with those in prior studies of older adults hospitalized with these three viral infections [18,26,27]. Many studies to date have assessed disease severity associated with these three types of viral infections, but the results of these studies have been highly varied.…”
Section: Discussionsupporting
confidence: 86%
“…ILI was defined as a combination of the following [18]: (ⅰ) at least one of the following systemic symptoms: fever or feverishness, headache, myalgia or malaise, and (ii) at least one of the following respiratory symptoms: cough, sore throat, or dyspnea. Pneumonia was defined based upon radiographic images indicating the presence of newly emergent consolidation or other infiltrates.…”
Section: Disease and Treatment Definitionsmentioning
confidence: 99%
“…In our study, 6.2%, 10.9%, and 17.3% of patients hospitalized with in uenza, RSV, and hMPV died within 30 days following admission, respectively. These mortality rates were consistent with those in prior studies of older adults hospitalized with these three viral infections [18,[26][27]. Many studies to date have assessed disease severity associated with these three types of viral infections, but the results of these studies have been inconsistent.…”
Section: Discussionsupporting
confidence: 85%
“…Other complications beyond pneumonia can also contribute to patient death. Loubet et al [18] found that hMPV infection was independently associated with acute cardiac failure. The results were in line with our ndings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation